The Effect of E-WOM and Consumer Satisfaction on Repurchase Interest in Azarine Sunscreen in Cirebon - Shelomita Shelomita; Anita Putri Lianie; Tesya Che Chilia; Lis Tatin Hernidatiatin (Journal Research of Social Science, Economics, and Management, 2024)
This study aims to determine the effect of Electronic Word Of Mouth and Consumer Satisfaction on Azarine Sunscreen in Cirebon. This study used descriptive analysis with a quantitative approach. The population in this study is consumers of Azarine Sunscreen in Cirebon with the number of samples used as many as 200 respondents. The sampling method used is nonprobability sampling with sampling techniques using purposive sampling, as well as data collection techniques using questionnaires. The analysis methods used are validity tests and reliability tests, classical assumption tests which include normality tests, multicollinearity tests and heteroscedasticity tests, and hypothesis tests that include linear regression analysis, F tests, t tests, and coefficients of determination (R2) with analytical tools using SPSS29 (Statistical Product and Service Solutions) applications. The results showed that Electronic Word Of Mouth had a significant effect on Azarine Sunscreen Repurchase Interest in Cirebon, Consumer Satisfaction had a significant effect on Azarine Sunscreen Repurchase Interest in Cirebon, and Electronic Word Of Mouth and Consumer Satisfaction variables simultaneously affected Azarine Sunscreen Repurchase Interest in Cirebon.